2022
DOI: 10.21138/dg.636
|View full text |Cite
|
Sign up to set email alerts
|

La trashumancia desde el ámbito geográfico: una propuesta práctica para profundizar en el patrimonio cultural

Abstract: La trashumancia es una práctica ganadera ancestral que lucha por pervivir mientras se apuntala su consideración como patrimonio inmaterial. Su conocimiento en el ámbito universitario se ha ceñido tradicionalmente a los estudios de veterinaria, pero las implicaciones culturales y patrimoniales que subyacen en la misma hacen que pueda ser foco de atención de otras áreas. Ello es lo que se pretende demostrar en el presente trabajo, donde se analizan los resultados de una propuesta práctica, basada en la conjugaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In addition, it was found that this low frequency of visits to the dehesa may be related to the scarce previous exposure to educational activities that allow students to learn about the traditions and trades that have characterized life in this environment. This fact suggests the need to promote experiences that allow contact with the intangible heritage [26], applied to the different educational levels [35] and that jointly involve actors from formal, nonformal and informal environments [84,88,89].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, it was found that this low frequency of visits to the dehesa may be related to the scarce previous exposure to educational activities that allow students to learn about the traditions and trades that have characterized life in this environment. This fact suggests the need to promote experiences that allow contact with the intangible heritage [26], applied to the different educational levels [35] and that jointly involve actors from formal, nonformal and informal environments [84,88,89].…”
Section: Discussionmentioning
confidence: 99%
“…They cover almost the entire Iberian Peninsula, with a length of more than 125,000 km and a surface area of 450,000 hectares [24]. Likewise, the transhumant system generated a great impact on the historical landscape due to the construction of various livestock infrastructure such as sheepfolds (a place where cattle are gathered at night), huts (shelter used by shepherds taking advantage of the natural resources of the environment), drinking troughs (a place for cattle to drink) or resting places (a place for cattle to rest), and the projection of a particular gastronomy and culinary practices, which today constitute valuable examples of the tangible and intangible heritage associated with this ancestral practice [25,26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation